Creating A Line Of Logic In The County Plan of Work - Glenn Israel; Steffany Dragon (EDIS, 2004)
This paper reviews the concept of logic and its role in developing a sound plan of work. This is followed by a discussion of the FAS2 components that define the program through logical situation and rationale statements and a description of the audience. This document is AEC 371 one of a series of the Agricultural Education and Communication Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date April 2004.